Cognitive Load Optimization in User Interface Design for Info Services - Balasm, Zaed; Rajan, S. S; Karpagham, C; Nuritdinovich, Muhidinov Ayubbek; Yusupov, Sardorbek; Maurya, Shyam (Indian Journal of Information Sources and Services, 2025)
Strategic management of cognitive load enhances user interface (UI) design in a two-fold manner, particularly in information services that require frequent use of sophisticated data. This paper addresses cognitive overload and elevated user experience by decomposing UI elements and information flow. The primary concern is having users cope with vital information within a reasonable timeframe, which is critical to productivity and overall satisfaction. We explore cognitive load theory, specifically its application in UI design regarding intrinsic, extraneous, and germane cognitive load. Through case studies and usability testing, we focus on visual hierarchies, navigation, and overall design consistency that advance feedback and content chunking to show the extreme reduction in mental effort. Also, cognitive load solutions that alter content and interaction based on user activity are advanced as novel adaptive interfaces. The paper frames real-world scenarios to illustrate assessing cognitive load in information service systems to aid UI decision-makers and developers. Emphasis on enabling real-time interface navigation supports optimal information retention and swift decision making. A systems approach focused on users' cognitive capabilities enables a UI design which ultimately makes information services more effective, efficient, and user-friendly.